A STUDY ON THE USE OF FECAL CHARACTERISTICS FOR FEED DIGESTIBILITY DETERMINATION IN GOAT - Santoso, S.A.B.; Puspitasari, G.; Muktiani, A.; Sunarso, S.; Purnomoadi, A. (Diponegoro University, 2015)
This study aimed to explore physical characteristics and its correlation to feed digestibility in goat.Sixteen Ettawah Grade goats in the second milk production periods and in the 4-5th month of lactationwere used in this study. The study was arranged with completely randomized block block design basedon milk production as replications. The goats were fed ration containing 16% of crude protein and 65%of total digestible nutrients (TDN). Some of crude protein content were supplied by urea. The treatmentswere control ration (without urea; T0), ration with 0.4% urea (T1), ration with 0.8% urea (T2), andration with 1.2% urea (T3). Parameters observed were feed digestibility, fecal extended level (FEL), andfecal rough particle distribution (FRPD). Data were analyzed using correlation-regression to find thecorrelation between fecal characteristics and feed digestibility. The results showed that urea content inthe rations up to 1.2% of dry matter did not affect dry mater digestibility, water content and fecalcharacteristics (FEL and FRPD). There were highly negative correlation (r= -0.665) between feeddigestibility and water content of feces as well as feed digestibility and FEL (r= -0.553), whilecorrelation between digestibility and FRDP was positive (r=0.608). The conclusion of this study waswater content, degree of FEL and FRPD can be used to determine the quality of feed. If feces composedof finer texture, dried and small particles indicated having better digestibility, while if feces composed ofrough texture, wet, and large particles indicated having low digestibility.